1997
DOI: 10.1159/000291869
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Analysis of Clinical and Morphological Prognostic Factors in Squamous Cell Carcinoma of the Vulva

Abstract: Clinical and histological data of 168 patients with squamous cell carcinoma of the vulva were analyzed with respect to survival. 151 patients underwent surgery, 12 patients were treated with primary radiation and in 5 patients no treatment was performed. Follow-up lasted from at least 2 up to 22 years’ posttreatment. In univariate analysis, the following factors were highly significant: presurgery lymph node status, tumor infiltration beyond the vulva, tumor grading, histological inguinal lymph node status, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
3
8
0
1
Order By: Relevance
“…This is in accordance with the Cochrane analysis of Ansik et al [22] and Van der Velden et al [23] reporting on the lower effectiveness of lymph node irradiation versus surgery. According to Smyczek-Gargya et al [6] patients with confined carcinoma to the vulva, with a tumor diameter up to 3 cm and without clinically suspicious lymph nodes, should be treated by wide excision/partial vulvectomy with ipsilateral lymphadenectomy. Ndubisi et al [7] analyzing retrospectively 135 patients over a 17-year period concluded that only lesion size and surgical status of the inguinal nodes were significant pre- dictors of disease-free survival, suggesting that the pathological status of the groin nodes at original surgery is definitely an important prognostic factor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the Cochrane analysis of Ansik et al [22] and Van der Velden et al [23] reporting on the lower effectiveness of lymph node irradiation versus surgery. According to Smyczek-Gargya et al [6] patients with confined carcinoma to the vulva, with a tumor diameter up to 3 cm and without clinically suspicious lymph nodes, should be treated by wide excision/partial vulvectomy with ipsilateral lymphadenectomy. Ndubisi et al [7] analyzing retrospectively 135 patients over a 17-year period concluded that only lesion size and surgical status of the inguinal nodes were significant pre- dictors of disease-free survival, suggesting that the pathological status of the groin nodes at original surgery is definitely an important prognostic factor.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of major prognostic factors (stage, grade of differentiation, node involvement, tumor diameter, depth of invasion and adequate tumor-free surgical margins) on overall and disease-free survival is undoubted [1][2][3]. However, only few reports are in the literature concern the possible impact of surgical dissection of groin nodes [6][7][8]. Patients from different clinics are referred to our department for gynecological radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…As pacientes com idade superior a 50 anos representaram 85% da amostra estudada, que tem como idade média 67,5 anos, o que concorda com outras casuísticas que indicam de 65 a 69 anos 11,12,14,15 . Torres Lobaton et al 11 relatam o caso da paciente mais jovem, com 14 anos.…”
Section: Discussionunclassified
“…The loss of Rb expression increased from FIGO stage I to IV, suggesting that Rb may play a role in tumor progression (81) . Another study showed progressive decrease of Rb2/p130 (a retinoblastoma-related protein) expression from non-neoplastic epithelial alterations through intraepithelial neoplasia to invasive vulvar (57) 122 Tumor site, depth of invasion, tumor size Boyce et al (56) 84 Clinical node status, depth of invasion, growth pattern Smyczek-Gargya et al (63) 168 Clinical node status, tumor size, depth of invasion, tumor grading carcinoma, suggesting a role for this tumor suppressor gene in vulvar carcinogenesis. There was no correlation between Rb2/p130 expression and the presence of lymph node metastases (82) .…”
Section: Cell Biologic Parametersmentioning
confidence: 99%